Concentration of Heavy Metal (Pb and Cu) in Sediment and Mangrove Avicennia Marina at Porong River Estuary, Sidoarjo, East Java - Ledhyane Ika Harlyan; Dwi Retnowati; Syarifah Hikmah Julinda Sari; Feni Iranawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
Abstract –The ability of mangrove (Avicennia) to absorb heavy metal has been known. This study aims to determine whether there are differences of absorption level of non-essential (Pb) essential (Cu) heavy metals in Avicennia marinafrom different location, based on distance of pollutants sources (downstream) toward to the mouth of Porong River Estuary at Sidoarjo. Results showed that accumulation of Pb in the roots and leaves was ranged from 0.0044 to 0.139 ppm and from 0.004 to 0.019 ppm respectively, while in sediment was ranged from 0.0560 to 0.0660 ppm. The accumulation of Cu in the roots and leaves was ranged from 0.07 to 0.415 ppm and 0.0318 to 0.2520 ppm while in sediments was from 0.2930 to 0.381 ppm. The highest concentration of Pb and Cu were found from sediments followed by roots and leaves. The high concentration of heavy metal (Pb and Cu) in the root is likely due to sediment size. The high concentration of heavy metal (Pb and Cu) in the root is likely due to sediment size. When the size is finer, heavy metal accumulation will be higher, although there was no significantly different from different location.